Personality Traits And Adjustment of Teachers - Dr. Shubhra Chaturvedi; Poonam Aggarwal (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
The present study was conducted to study the personality traits and adjustment of teachers. For this purpose certain objectives were framed which were translated in to specific hypotheses. The sample consisted of 200 teachers in which 100 were of government school (50 male and 50 female) and 100 were from private schools (50 male and 50 female). The results of this study revealed that private school teachers have better personality traits than government school teachers and also government school teachers show better adjustment than private school teachers. The results of this study also revealed that the government school female teachers have better personality traits than government school male teachers and government school male teachers show better adjustment than government school female teachers and private school female teachers have better personality traits than private school male teachers and the private school female teachers have better personality traits than private school male teachers.